The mechanical properties ofacrylonitrile-butadiene-styrene (abs) / nylon 6 / talc composites - A.Rahman, Azura Hanis; Azman, Hassan (2007)
Blending is capable of providing materials which extend the useful properties beyond the range that can be obtained from single polymer equivalents. But on the other hand, reinforcement has received considerable attention for many years in polymer world to come up with new material with unique properties and low cost. In this study, Acrylonitrile-Butadiene-Styrene (ABS) and nylon 6 reinforced with talc were prepared in different ratios and it went through twin screw extruder, injection moulding and was tested with three different tests: tensile test, flexural test and Izod impact test. A super high impact ABS was used and different concentration of talc were incorporated into the blends to study the mechanical properties of the composites: tensile, flexural and impact properties. Accurately, this study is done toinvestigate the optimum blending ratio for ABS and nylon 6 and also to study the effect of talc concentration as filler on ABS/nylon 6 blends. From the research, it was found that tensile strength and Young Modulus increased with the increasing of talc content in ABS/ nylon 6 blends. Flexural modulus increased with increasing talc content but the flexural strength decreased with filler loading. However, with increasing talc composition the composites gave decreasing impact strength values.